Tweeterm als gem. factor (3)

Hoofdmenu Eentje per keer 

Zonder de gemeenschappelijke tweeterm af en 'kuis op'.

  1. \((4x+7)^2-(16x+28)\)
  2. \((x+1)(x+4)-(3x-4)(x+1)\)
  3. \((y-8)(y+5)+(2y+5)(y-8)\)
  4. \((3s+1)^2+(12s+4)\)
  5. \((4s+7)(s+8)-(4s+7)(3s-3)\)
  6. \((a-1)(a-8)-(4a-8)(a-1)\)
  7. \((s-6)(s+9)-(5s+6)(s-6)\)
  8. \((x-1)(x+1)-(3x-4)(x-1)\)
  9. \((b+2)(b-2)-(4b+2)(b+2)\)
  10. \((8q+3)^2-(40q+15)\)
  11. \((7a-7)(a-9)+(7a-7)(4a+7)\)
  12. \((7a+9)^2-(14a+18)\)

Zonder de gemeenschappelijke tweeterm af en 'kuis op'.

Verbetersleutel

  1. \((4x+7)^2-(16x+28)\\=(4x+7)(4x+7)-4(4x+7)\\=(4x+3)(4x+7)\)
  2. \((x+1)(x+4)-(3x-4)(x+1)\\=(x+1)(x+4-3x+4)\\=(x+1)(-2x+8)\)
  3. \((y-8)(y+5)+(2y+5)(y-8)\\=(y-8)(y+5+2y+5)\\=(y-8)(3y+10)\)
  4. \((3s+1)^2+(12s+4)\\=(3s+1)(3s+1)+4(3s+1)\\=(3s+5)(3s+1)\)
  5. \((4s+7)(s+8)-(4s+7)(3s-3)\\=(4s+7)(s+8-3s+3)\\=(4s+7)(-2s+11)\)
  6. \((a-1)(a-8)-(4a-8)(a-1)\\=(a-1)(a-8-4a+8)\\=(a-1)(-3a+0)\)
  7. \((s-6)(s+9)-(5s+6)(s-6)\\=(s-6)(s+9-5s-6)\\=(s-6)(-4s+3)\)
  8. \((x-1)(x+1)-(3x-4)(x-1)\\=(x-1)(x+1-3x+4)\\=(x-1)(-2x+5)\)
  9. \((b+2)(b-2)-(4b+2)(b+2)\\=(b+2)(b-2-4b-2)\\=(b+2)(-3b-4)\)
  10. \((8q+3)^2-(40q+15)\\=(8q+3)(8q+3)-5(8q+3)\\=(8q-2)(8q+3)\)
  11. \((7a-7)(a-9)+(7a-7)(4a+7)\\=(7a-7)(a-9+4a+7)\\=(7a-7)(5a-2)\)
  12. \((7a+9)^2-(14a+18)\\=(7a+9)(7a+9)-2(7a+9)\\=(7a+7)(7a+9)\)
Oefeningengenerator vanhoeckes.be/wiskunde 2022-06-27 07:25:35